Hydrochlorothiazide-induced hyperuricaemia in the Pharmacogenomic Evaluation of Antihypertensive Responses (PEAR) study - Vandell, Alexander G. (2014)
OBJECTIVE: Elevations in uric acid (UA) and the associated hyperuricaemia are commonly observed secondary to treatment with thiazide diuretics. We sought to identify novel single-nucleotide polymorphisms (SNPs) associated with hydrochlorothiazide (HCTZ)-induced elevations in UA and hyperuricaemia. METHODS: A genome-wide association study of HCTZ-induced changes in UA was performed in Caucasian and African American participants from the Pharmacogenomic Evaluation of Antihypertensive Response (PEAR) study who were treated with HCTZ monotherapy. Suggestive SNPs were replicated in Caucasians and African Americans from the PEAR study who were treated with HCTZ add-on therapy. Replicated regions were followed up through expression and pathway analysis. RESULTS: Five unique gene regions were identified in African Americans (LUC7L2, ANKRD17/COX18, FTO, PADI4 and PARD3B) and one region was identified in Caucasians (GRIN3A). Increases in UA of up to 1.8 mg/dL were observed following HCTZ therapy in individuals homozygous for risk alleles, with heterozygotes displaying an intermediate phenotype. Several risk alleles were also associated with an increased risk of HCTZ-induced clinical hyperuricaemia. A composite risk score, constructed in African Americans using the ‘top’ SNP from each gene region, was strongly associated with HCTZ-induced UA elevations (P = 1.79×10(−7)) and explained 11% of the variability in UA response. Expression studies in RNA from whole blood revealed significant differences in expression of FTO by rs4784333 genotype. Pathway analysis showed putative connections between many of the genes identified through common microRNAs. CONCLUSION: Several novel gene regions were associated with HCTZ-induced UA elevations in African Americans (LUC7L2, COX18/ANKRD17, FTO, PADI4 and PARD3B) and one region was associated with these elevations in Caucasians (GRIN3A).